Assignment 19 24

#$&*

course mth 158

7/23/13 3:26pm

If your solution to stated problem does not match the given solution, you should self-critique per instructions at http://vhcc2.vhcc.edu/dsmith/geninfo/labrynth_created_fall_05/levl1_22/levl2_81/file3_259.htm.

Your solution, attempt at solution:

If you are unable to attempt a solution, give a phrase-by-phrase interpretation of the problem along with a statement of what you do or do not understand about it. This response should be given, based on the work you did in completing the assignment, before you look at the given solution.

019. `* 19

*********************************************

Question: * 2.4.10 (was 2.4.30). (0,1) and (2,3) on diameter **** What are the center, radius and equation of the indicated circle?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Must use the midpoint formula to find the center of the circle.

m = ( (x1 + x2) / 2 , (y1 + y2) / 2 )

m = ( (0 + 2)/2 , (1+3)/2 )

m = ( 2/2 , 4/2 )

m = (1, 2) This is the center of the circle

To find the radius I used the distance formula to find the distance between the center and another given point.

d = sqrt [(x2 - x1)^2 + (y2 - y1)^2 ]

d = sqrt [(2 - 1)^2 + (3 - 2)^2 ]

d = sqrt (1 + 1)

d = sqrt (2)

Plugging this information into the standard formula for a circle

(h, k) = (1, 2) r = sqrt (2)

(x - h)^2 + (y - k)^2 = r^2

(x - 1)^2 + (y - 2)^2 = 2

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *

The center of the circle is at the midpoint between the endpoints of the diameter, at x coordinate (0 + 2) / 2 = 1 and y coordinate (1 + 3) / 2 = 2. i.e., the center is at (1, 2).

Using these coordinates, the general equation (x-h)^2 + (y-k)^2 = r^2 of a circle becomes

(x-1)^2 + (y-2)^2 = r^2.

Substituting the coordinates of the point (0, 1) we get

(0-1)^2 + (1-2)^2 = r^2 so that

r^2 = 2.

Our equation is therefore

(x-1)^2 + (y - 2)^2 = 2.

You should double-check this solution by substituting the coordinates of the point (2, 3).

Another way to find the equation is to simply find the radius from the given points:

The distance from (0,1) to (2,3) is sqrt( (2-0)^2 + (3-1)^2 ) = sqrt(4 + 4) = sqrt(8) = 2 * sqrt(2).

This distance is a diameter so that the radius is 1/2 (2 sqrt(2)) = sqrt(2). *

The equation of a circle centered at (1, 2) and having radius sqrt(2) is

(x-1)^2 + (y - 2)^2 = (sqrt(2)) ^ 2 or

(x-1)^2 + (y - 2)^2 = 2

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: * 2.4.14 / 16 (was 2.4.36). What is the standard form of a circle with (h, k) = (1, 0) with radius 3?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(x - 1)^2 + (y - 0)^2 = 9

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The standard form of a circle is (x - h)^2 + (y - k)^2 = r^2, where the center is at (h, k) and the radius is r.

In this example we have (h, k) = (1, 0). We therefore have

(x-1)^2 +(y - 0)^2 = 3^2.

This is the requested standard form.

This form can be expanded and simplified to a general quadratic form. Expanding (x-1)^2 and squaring the 3 we get

x^2 - 2x +1+y^2 = 9

x^2 - 2x + y^2 = 8.

However this is not the standard form.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): Ok, though I did not leave the 3^2, but instead changed it to 9

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: * 2.4.22 / 24 (was 2.4.40). x^2 + (y-1)^2 = 1 **** Give the center and radius of the circle and explain how they were obtained. In which quadrant(s) was your graph and where did it intercept x and/or y axes?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

x^2 + (y-1)^2 = 1

(x - 0)^2 + (y - 1)^2 = 1

(h, k) = (0, 1) r = 1

x-int

x^2 + (0 - 1)^2 = 1

x^2 + 1 = 1

x^2 = 0

x-int is (0, 0)

y-int

0^2 + (y - 1)^2 = 1

(y - 1)^2 = 1

y - 1 = +/- 1

y - 1 = 1 y - 1 = -1

y = 2 y = 0

y-ints are (0, 2) and (0,0)

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The standard form of a circle is (x - h)^2 + (y - k)^2 = r^2, where the center is at (h, k) and the radius is r.

In this example the equation can be written as

(x - 0)^2 + (y-1)^2 = 1

So h = 0 and k = 1, and r^2 = 1. The center of the is therefore (0, -1) and r = sqrt(r^2) = sqrt(1) = 1.

The x intercept occurs when y = 0:

x^2 + (y-1)^2 = 1. I fy = 0 we get

x^2 + (0-1)^2 = 1, which simplifies to

x^2 +1=1, or

x^2=0 so that x = 0. The x intercept is therefore (0, 0).

The y intercept occurs when x = 0 so we obtain

0 + (y-1)^2 = 1, which is just (y - 1)^2 = 1. It follow that

(y-1) = +-1.

If y - 1 = 1 we get y = 2; if y - 1 = -1 we get y = 0. So the y-intercepts are

(0,0) and (0, 2)

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: * 2.4.32 / 34 (was 2.4.48). 2 x^2 + 2 y^2 + 8 x + 7 = 0 **** Give the center and radius of the circle and explain how they were obtained. In which quadrant(s) was your graph and where did it intercept x and/or y axes?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

2 x^2 + 2 y^2 + 8 x + 7 = 0

2 x^2 + 8x + 2y^2 = -7

x^2 + 4x + y^2 = -7/2

(x^2 + 4x + 4) + y^2 = -7/2 + 4

(x + 2)^2 + (y + 0)^2 = 1/2

(h, k) = (-2, 0) r = 1/4

x-int

(x + 2)^2 + 0^2 = 1/2

(x + 2)^2 = 1/2

x + 2 = +/- sqrt (1/2)

x + 2 = sqrt (1/2) x + 2 = - sqrt (1/2)

x = -1.29 x = -2.71

y-int

(0 +2)^2 + y^2 = 1/2

4 + y^2 = 1/2

y^2 = -7/2

This is an impossible situation because of the negative sign; no y-int

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * We first want to complete the squares on the x and y terms:

Starting with

2x^2+ 2y^2 +8x+7=0 we group x and y terms to get

2x^2 +8x +2y^2 =-7. We then divide by the common factor 2 to get

x^2 +4x + y^2 = -7/2. We complete the square on x^2 + 4x, adding to both sides (4/2)^2 = 4, to get

x^2 + 4x + 4 + y^2 = -7/2 + 4. We factor the expression x^2 + 4x + 4 to obtain

(x+2)^2 + y^2 = 1/2.

We interpret our result:

The standard form of the equation of a circle is

(x - h)^2 + (y - k)^2 = r^2,

where the center is the point (h, k) and the radius is r.

Matching this with our equation

(x+2)^2 + y^2 = 1/2

we find that h = -2, k = 0 and r^2 = 1/2. We conclude that

the center is (-2,0)

the radius is sqrt (1/2).

To get the intercepts:

We use (x+2)^2 + y^2 = 1/2

If y = 0 then we have

(x+2)^2 + 0^2 = 1/2

(x+2)^2 = 1/2

(x+2) = +- sqrt(1/2)

x + 2 = sqrt(1/2) yields x = sqrt(1/2) - 2 = -1.3 approx.

x + 2 = -sqrt(1/2) yields x = -sqrt(1/2) - 2 = -2.7 approx

(note: The above solutions are approximate. The exact solutions can be expressed according to the following:

sqrt(1/2) = 1 / sqrt(2) = sqrt(2) / 2, found by rationalizing the denominator; so sqrt(1/2) - 2 = sqrt(2)/2 - 2 = (sqrt(2) - 4) / 2. This is an exact solution for one x intercept. The other is (-sqrt(2) - 4) / 2.

If x = 0 we have

(0+2)^2 + y^2 = 1/2

4 + y^2 = 1/2

y^2 = 1/2 - 4 = -7/2.

y^2 cannot be negative so there is no y intercept. This is consistent with the fact that a circle centered at (-2, 0) with radius sqrt(1/2) lies entirely to the right of the y axis. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK

*********************************************

Question: * 2.4.40 / 30 (was 2.4.54). General equation if diameter contains (4, 3) and (0, 1). **** Give the general equation for your circle and explain how it was obtained.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

To find the center must find the midpoint:

m = ( (x1 + x2)/2 , (y1 + y2)/2 )

m = ( (0+ 4) / 2 , (3 + 1) / 2 )

m = (4/2, 4/2 )

m = (2, 2)

Now find the radius by plugging in the center and another given point

(x - h)^2 + (y - k)^2 = r^2

(0 - 2) ^2 + (1-2)^2 = r^2

4 + 1 = r^2

5 = r^2

sqrt (5) = r

Plugging back in

(x - 2)^2 + (y-2)^2 = 5

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * The center of the circle is the midpoint between the two points, which is ((4+0)/2, (3+1)/2) = (2, 2).

The radius of the circle is the distance from the center to either of the given points. The distance from (2, 2) to (0, 1) is sqrt( (2-0)^2 + (2-1)^2 ) = sqrt(5).

The equation of the circle is therefore found from the standard equation, which is

(x - h)^2 + (y - k)^2 = r^2,

where the center is the point (h, k) and the radius is r.

Since the center is at (2, 2) and the radius is sqrt(5), our equation is

(x-2)^2 + (y-2)^2 = (sqrt(5))^2 or

(x-2)^2 + (y-2)^2 = 5. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): OK

------------------------------------------------

Self-critique Rating: OK"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#Good work. Let me know if you have questions. &#